Avaliação da resistência de união adesiva à dentina em diferentes tempos e soluções de armazenamento - Oenning, Victor Patrick (2019)
Purpose: To evaluate the effect of bovine teeth storage in 4 different solutions: distilled water (DW), saline (S), 0.5% chloramine (C) and 0.1% thymol(T), when frozen for 4 different times: 1 week, 1 month, 3 and 6 months, on bond strength to dentin. Materials and Methods: 136 bovine incisors were divided into 16 experimental groups (n = 8), and compared to the one observed in immediately extracted teeth that were not stored, the control group (CG), totaling 17 groups. The specimens were made with conventional adhesive Adper Single Bond 2 (3M ESPE, St Paul, MN, USA) and Opallis Flow composite (Dentscare LTDA, Joinville, SC, BRA) after different storage periods. After 1 week, the specimens were tested in a universal testing machine (EMIC DL 500, São José dos Pinhais, PR, BRA); the rupture force was recorded in N and, according to the area of the adhesive interface, converted into MPa. Results: The groups stored in DW had the lowest values at all times, and 0.5% chloramine was the most stable solution up to 3 months. Conclusion: It can be concluded that different solutions and storage times interfere on the bond strength to dentin.